2020
DOI: 10.3390/molecules25194354
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestion and Fermentation by Human Fecal Microbiota of Polysaccharides from Flaxseed

Abstract: The digestion of flaxseed polysaccharides (FSP) in simulated saliva, gastric and small intestine conditions was assessed, as well as in vitro fermentation of FSP by human gut microbiota. FSP was not degraded in the simulated digestive systems (there was no change in molecular weight or content of reducing sugars), indicating that ingested FSP would reach the large intestine intact. Changes in carbohydrate content, reducing sugars and culture pH suggested that FSP could be broken down and used by gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Furthermore, the FC6 h sample from the control group had the lowest total SCFA content, but it was still higher than the sample without fermentation (F0 h) ( p < 0.05). This reason might be that gut microbes generate SCFAs by fermentation of dietary fibers in FJR, which is reported by several similar studies previously ( 34 36 ).…”
Section: Resultssupporting
confidence: 55%
“…Furthermore, the FC6 h sample from the control group had the lowest total SCFA content, but it was still higher than the sample without fermentation (F0 h) ( p < 0.05). This reason might be that gut microbes generate SCFAs by fermentation of dietary fibers in FJR, which is reported by several similar studies previously ( 34 36 ).…”
Section: Resultssupporting
confidence: 55%
“…In vivo studies in mice with LAB-fermented goat milk ( Chen et al, 2020 ) and kefir ( Hsu et al, 2018 ) also observed an increased Firmicutes to Bacteroidetes (F/B) ratio in the treatment group. On the other hand, other polysaccharides, from okra ( Wu et al, 2021c ), flaxseed ( Zhou et al, 2020 ), and mushrooms ( Liu et al, 2021 ), observed increased Bacteroidetes abundance, and reduced Firmicutes , with a lower F/B ratio. Polyphenols act as prebiotics in the gut and have also been shown to influence F/B ratio through the inhibition of certain bacterial species ( Loo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major insoluble fiber fraction consists of cellulose and lignin [ 11 ]. The main soluble fiber from flaxseed has been reported to be a heterogeneous polysaccharide consisting of neutral arabinoxylan and acidic rhamnose [ 12 ]. This flaxseed polysaccharide exhibited good antioxidant activities in vitro and reduced elevated blood glucose in rats [ 13 ].…”
Section: Introductionmentioning
confidence: 99%